Artificial Intelligence and the Transformation of Catholic Religious Authority and Learning Practices - Simbolon, Erikson; Handayani Ginting, Monika; Simarmata, Petrus; Tibo, Paulinus (Prodi Studi Agama-Agama, 2026)
This study examines the role of Artificial Intelligence (AI) in reshaping religious authority and learning practices within Catholic education, focusing on the subject of the Church as the People of God. Employing a qualitative research design based on Creswell’s approach, the study seeks to explore the lived experiences of teachers and students in engaging with AI as part of religious learning processes. Data were collected through in-depth interviews, classroom observations, and document analysis at SMA Katolik 2 Kabanjahe, North Sumatra Province, involving two Catholic Religious Education teachers, thirty students, and the school principal. Data analysis followed the stages of data reduction, data display, and interactive conclusion drawing. The findings indicate that AI does not merely function as a pedagogical tool, but actively transforms patterns of religious learning and the mediation of ecclesial authority in the classroom. AI facilitates more contextual theological explanations, supports simulated pastoral dialogues, and provides visual resources that strengthen students’ conceptual and reflective understanding of the Church’s identity as the People of God. At the same time, the integration of AI reconfigures the role of teachers from primary transmitters of knowledge to mediators of meaning, interpretation, and ecclesial values. Students demonstrate increased learning motivation, deeper faith reflection, and more critical engagement with religious content. However, this transformation also generates challenges, including technological dependency, unequal digital literacy, and the need for continuous ethical and ecclesial guidance to ensure that AI-mediated learning remains aligned with Catholic values and religious authority structures